North American ginseng influences adipocyte–macrophage crosstalk regulation of inflammatory gene expression - Jaime Garbett; Sarah A.F. Wilson; Jessica C. Ralston; Anna A. De Boer; Ed M.K. Lui; David C. Wright; David M. Mutch (Journal of Ginseng Research, 2016)
Background: Adipocyte–macrophage communication plays a critical role regulating white adipose tissue (WAT) inflammatory gene expression. Because WAT inflammation contributes to the development of metabolic diseases, there is significant interest in understanding how exogenous compounds regulate the adipocyte–macrophage crosstalk. An aqueous (AQ) extract of North American (NA) ginseng (Panax quinquefolius) was previously shown to have strong inflammo-regulatory properties in adipocytes. This study examined whether different ginseng extracts influence adipocyte–macrophage crosstalk, as well as WAT inflammatory gene expression. Methods: The effects of AQ and ethanol (EtOH) ginseng extracts (5 μg/mL) on adipocyte and macrophage inflammatory gene expression were studied in 3T3-L1 and RAW264.7 cells, respectively, using real-time reverse transcription polymerase chain reaction. Adipose tissue organ culture was also used to examine the effects of ginseng extracts on epididymal WAT (EWAT) and inguinal subcutaneous WAT (SWAT) inflammatory gene expression. Results: The AQ extract caused significant increases in the expression of common inflammatory genes (e.g., Mcp1, Ccl5, Tnf-α, Nos2) in both cell types. Culturing adipocytes in media from macrophages treated with the AQ extract, and vice versa, also induced inflammatory gene expression. Adipocyte Ppar-γ expression was reduced with the AQ extract. The AQ extract strongly induced inflammatory gene expression in EWAT, but not in SWAT. The EtOH extract had no effect on inflammatory gene expression in either both cell types or WAT. Conclusion: These findings provide important new insights into the inflammo-regulatory role of NA ginseng in WAT.